Polner Ödön ismeretlen előadása az 1848. évi áprilisi törvényekről - Schweitzer, Gábor; Szente, Zoltán (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
Professor Ödön Polner (1865-1961) was one of the outstanding scholars of Hungarian public law. His legacy includes the manuscript of a lecture he gave in 1948, in which he reviewed the basic laws adopted in the first phase of the Hungarian Revolution of 1848. Within the framework of the historical constitution, these laws laid the foundations of nationalism and bourgeois constitutionalism in Hungary in the middle of the 19th century. Below, after a short description of Polner’s professional career and some introductory remarks, we publish the text of the lecture given in 1948.